Gemini/GMOS imaging of globular clusters in the Virgo galaxy NGC 4649 (M60) - Forbes, Duncan A. (2004)
We present Sloan g and i imaging from the Gemini Multi-object Spectrograph (GMOS) instrument on the Gemini North telescope for the globular cluster (GC) system around the Virgo galaxy NGC 4649 (M60). Our three pointings, taken in good seeing conditions, cover an area of about 90 square arcmin. We detect 2151 unresolved sources. Applying colour and magnitude selection criteria to this source list gives 995 candidate GCs. Our source list is greater than 90 per cent complete to a magnitude of i = 23.6, and has little contamination from background galaxies. We find fewer than half a dozen potential ultracompact dwarf galaxies around NGC 4649. Foreground extinction from the nearby spiral NGC 4647 is limited to be AV < 0.1. We confirm the bimodality in the GC colour distribution found by earlier work using Hubble Space Telescope/WFPC2 imaging. As is commonly seen in other galaxies, the red GCs are concentrated towards the centre of the galaxy, having a steeper number density profile than the blue GC subpopulation. The varying ratio of red-to-blue GCs with radius can largely explain the overall GC system colour gradient. The underlying galaxy starlight has a similar density profile slope and colour to the red GCs. This suggests a direct connection between the galaxy field stars and the red GC subpopulation. We estimate a total GC population of 3700 ± 900, with the uncertainty dominated by the extrapolation to larger radii than observed. This total number corresponds to a specific frequency SN = 4.1 ± 1.0. Future work will present properties derived from GMOS spectra of the NGC 4649 GCs.